Age and the clinical profile of idiopathic mitral valve prolapse. - Hickey, A J (1986)
The prevalence of mitral valve prolapse was determined in two independent populations (6887 consecutive adults and children referred for echocardiography during a three year period and 206 non-referred first degree relatives of 65 patients with mitral valve prolapse). In the 118 adults with echocardiographic evidence of prolapse those aged greater than or equal to 50 years were significantly more likely to have pansystolic murmurs and increased echocardiographic dimensions than those aged less than 50 years; and patients with complications of mitral valve prolapse were significantly older than those without. In the population referred for echocardiography and in the non-referred relatives there was a significant increase in prevalence in the two decades after adolescence (20-39 years) compared with that in the first two decades. The data suggest that prolapse principally becomes manifest in late adolescence when the growth spurt is complete and that thereafter the severity of prolapse increases with age in an important subset of patients. The latter findings accord with the predictions of the response to injury hypothesis for the pathogenesis of progressive changes.